Catheter-directed thrombolytic therapy combined with angioplasty for hepatic vein obstruction in Budd-Chiari syndrome complicated by thrombosis - ZHANG, QINGQIAO; XU, HAO; ZU, MAOHENG; GU, YUMING; WEI, NING; WANG, WENLIANG; GAO, ZHIKANG; SHEN, BIN (Experimental and therapeutic medicine, 2013)
The aim of this study was to assess the efficacy and safety of catheter-directed thrombolysis combined with angioplasty in the treatment of hepatic vein obstruction in Budd-Chiari syndrome (BCS) complicated by thrombosis. In 14 cases of BCS, the patients with hepatic vein obstruction complicated by thrombosis who underwent catheter-directed urokinase thrombolysis, balloon dilatation and/or stent placement were followed up with an ultrasound examination of the liver. Among the 13 cases of successful treatment, one hepatic vein was recanalized in 12 patients (right hepatic vein, seven cases; left hepatic vein, three cases; middle hepatic vein, one case and accessory hepatic vein, one case) and two hepatic veins (right and left) were recanalized in one patient without serious complications, such as bleeding and pulmonary embolism. There was one patient in whom the treatment was unsuccessful. During an average follow-up period of 24.8±19.6 months, hepatic vein restenosis was observed in one patient in the sixth month after opperation; however, a successful result was obtained following a second balloon dilatation. The remaining 12 patients did not demonstrate any recurrence of restenosis or thrombosis. Catheter-directed thrombolysis combined with angioplasty was observed to be an effective and safe method for the treatment of hepatic vein obstruction in BCS complicated by thrombosis.